A recognizable systemic connective tissue disorder with polyvalvular heart dystrophy and dysmorphism associated with TAB2 mutations. Issue 1 (21st August 2017) - Ritelli, M.; Morlino, S.; Giacopuzzi, E.; Bernardini, L.; Torres, B.; Santoro, G.; Ravasio, V.; Chiarelli, N.; D'Angelantonio, D.; Novelli, A.; Grammatico, P.; Colombi, M.; et al.
Abstract : Deletions encompassing TAK1‐binding protein 2 ( TAB2 ) associated with isolated and syndromic congenital heart defects. Rare missense variants are found in patients with a similar phenotype as well as in a single individual with frontometaphyseal dysplasia. We describe a family and an additional sporadic patient with polyvalvular heart disease, generalized joint hypermobility and related musculoskeletal complications, soft, velvety and hyperextensible skin, short limbs, hearing impairment, and facial dysmorphism. In the first family, whole‐exome sequencing (WES) disclosed the novel TAB2 c.1398dup (p.Thr467Tyrfs*6) variant that eliminates the C‐terminal zinc finger domain essential for activation of TAK1 (TGFβ‐activated kinase 1)‐dependent signaling pathways. The sporadic case carryed a ~2 Mb de novo deletion including 28 genes also comprising TAB2 . This study reveal an association between TAB2 mutations and a phenotype resembling Ehlers‐Danlos syndrome with severe polyvalvular heart disease and subtle facial dysmorphism. Our findings support the existence of a wider spectrum of clinical phenotypes associated with TAB2 perturbations and emphasize the role of TAK1 signaling network in human development. Abstract : Identification by whole‐exome sequencing of a novel frameshift mutation and a de novo deletion encompassing TAB2 in 2 families with polyvalvular heart disease and a constellation of systemic findings, mainly comprising joint hypermobility and related musculoskeletal complications, soft, velvety and hyperextensible skin, short limbs, hearing impairment, and facial dysmorphism.